The Predictability of Short-Horizon Stock Returns - Mase, Bryan (Review of Finance, 1999)
This examines the predictability of short-horizon stock returns in the UK. We show that the subsequent return reversal of previous extreme performers is unlikely to be caused by either lead-lag effects or inventory imbalances, the most likely explanation being market overreaction. A market or trading based explanation is reinforced by the finding that these return reversals are asymmetric, being less significant after bad news. Further, we find that the lower transacting stocks exhibit the stronger return reversals, in direct contrast to both the existing US evidence and the implication that liquidity effects can explain the return reversals. JEL Classification: G10, G11, G12